Principal Management in Teacher Guidance at Muhammadiyah 8 High School, Palembang - Fitrah Yeni; Alhadi Yan Putra; Pahlawan Pahlawan (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Principal management plays a crucial role in the development of teachers, significantly influencing their professional competence and performance in carrying out educational responsibilities. This study aims to describe and analyze (1) principal management strategies in teacher development, (2) obstacles encountered during the implementation of these strategies, and (3) solutions to overcome the identified obstacles. The research was conducted at SMA Muhammadiyah 8 Palembang using a qualitative descriptive method. Data collection techniques included interviews with school leaders and teachers, direct observations of school activities, and document analysis related to teacher development programs. Data were analyzed using an interactive model consisting of data collection, data reduction, data presentation, and conclusion drawing. The findings show that principal management in teacher development involves structured planning, implementation of professional training, performance evaluation, mentoring programs, and the establishment of collaborative work teams aligned with the school's vision and mission. However, several obstacles were identified in the implementation process, such as limited human and financial resources, differences in teacher readiness and motivation, resistance to new policies or changes, and difficulties in maintaining consistent monitoring and supervision. To address these challenges, school leaders have adopted various strategies, including intensifying teacher training and mentoring, promoting teamwork among staff, utilizing digital technology to support learning and supervision, and building partnerships with external education stakeholders. Additionally, regular evaluations and feedback mechanisms are conducted to ensure that teacher development programs remain responsive to current needs. This research emphasizes the importance of effective leadership and adaptive strategies in fostering continuous professional growth for teachers within the school environment.